2017
DOI: 10.1039/c7ta06895f
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-free, graphene based anodes and air cathodes for single chamber microbial fuel cells

Abstract: In this work graphene-based aerogel anodes and graphene/stainless steel cathodes have been optimised as platinum-free electrodes in Rhodopseudomonas palustris microbial fuel cells, achieving a maximum power output of ∼3.5 W m–3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 85 publications
(109 reference statements)
0
30
0
Order By: Relevance
“…The world’s increasing population and energy demand and the recognition of the environmental consequences and limited availability of fossil fuels have driven extensive research into the development of renewable energy sources, including biologically based ones [ 1 ]. These technologies include Microbial Fuel Cells (MFCs), which are bioelectrochemical systems that exploit the electron-producing respiration processes of heterotrophic microbes [ 2 , 3 ]. Biophotovoltaics (BPVs), by contrast, function as biological solar cells, using the photosynthetic activity of microalgae or cyanobacteria to harvest solar energy and generate an electrical current [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The world’s increasing population and energy demand and the recognition of the environmental consequences and limited availability of fossil fuels have driven extensive research into the development of renewable energy sources, including biologically based ones [ 1 ]. These technologies include Microbial Fuel Cells (MFCs), which are bioelectrochemical systems that exploit the electron-producing respiration processes of heterotrophic microbes [ 2 , 3 ]. Biophotovoltaics (BPVs), by contrast, function as biological solar cells, using the photosynthetic activity of microalgae or cyanobacteria to harvest solar energy and generate an electrical current [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It will therefore be important to consider other possible cathodes. Call et al . showed that a MFC using the anoxygenic photosynthetic bacterium Rhodopseudomonas palustris in the anode was able to function with an air cathode of graphene‐coated stainless steel.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…[60] It will therefore be important to consider other possible cathodes. Call et al [96] showed that a MFC using the anoxygenic photosynthetic bacterium Rhodopseudomonas palustris in the anode was able to function with an air cathode of graphene-coated stainless steel. Although the power output was around a quarter of that with a platinum cathode, it was around 500 times greater than that with a stainless-steel cathode.…”
Section: Future Improvements For Bpv Outputmentioning
confidence: 99%
“…The electrical and heating properties of the GNP fabric are characterized on a 2 Â 2 cm sample, thus revealing a sheet resistance of R s B 169 O and conductivity of s B 778.6 S m À1 , which is consistent with the conductivity values reported by previous works. 35,38 The heating properties of the GNP fabric were investigated by monitoring the evolution of the temperature by an infrared camera (see methods) as a function of the applied voltage (V GNP ) across the GNP fabric (between 2 V and 16 V; Fig. 3).…”
Section: Electrical and Thermal Characterization Of The Gnp Fabricmentioning
confidence: 99%
“…However, the conductivity of the monofilament is low (1 Â 10 À2 S cm À1 ), requiring a high voltage to induce a thermochromic colour change and becoming unsuitable for wearable applications. Graphene and graphene nano-platelets (GNPs) have been the focus of intense research as suitable materials for electric heating, 33 as well as biocompatible 34,35 and wearable electronics. 6,36,37 Based on previous works on UV-induced thermochromic textiles 24 using rhodamine B ethylenediamine derivative molecules, we demonstrated a screen-printed electro-thermochromic textile (ET) on the cotton fabric comprising a UV-induced thermochromic polyurethane layer based on the rhodamine B ethylenediamine derivative molecules and GNP electrodes.…”
Section: Introductionmentioning
confidence: 99%